2018
DOI: 10.1111/inm.12459
|View full text |Cite
|
Sign up to set email alerts
|

Patient receipt of smoking cessation care in four Australian acute psychiatric facilities

Abstract: This study aimed to report the receipt of smoking care, and associated clinical and smoking characteristics among smokers admitted to four public psychiatric inpatient facilities in New South Wales, Australia. Between October 2012 and July 2014, adult smokers (N = 236) were surveyed during admission to and 1 month following discharge from the facilities. Measures of smoking care receipt were reported descriptively, and logistic regression analyses were used to explore characteristics associated with care recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Previous research in psychiatry settings reported the routine provision of brief smoking cessation advice at moderate levels and smoking status documentation as low as 50%, even after implementing system change interventions, intensive staff training and highly targeted smoking cessation interventions (Lappin et al, 2020;Metse et al, 2018;Prochaska et al, 2004;Williams et al, 2015;Wye et al, 2009Wye et al, , 2010Wye et al, , 2017Young et al, 2022). However, our study found high smoking status documentation (88%) prior to the system change intervention, likely related to new laws in 2015 that prohibited smoking at Queensland hospitals, which motivated improved smoking status documentation for inpatients and development of the Pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in psychiatry settings reported the routine provision of brief smoking cessation advice at moderate levels and smoking status documentation as low as 50%, even after implementing system change interventions, intensive staff training and highly targeted smoking cessation interventions (Lappin et al, 2020;Metse et al, 2018;Prochaska et al, 2004;Williams et al, 2015;Wye et al, 2009Wye et al, , 2010Wye et al, , 2017Young et al, 2022). However, our study found high smoking status documentation (88%) prior to the system change intervention, likely related to new laws in 2015 that prohibited smoking at Queensland hospitals, which motivated improved smoking status documentation for inpatients and development of the Pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital admissions present an opportunity to deliver smoking cessation interventions (Rigotti et al, 2012) and psychiatry inpatient units are uniquely positioned to support people with SMI who smoke with evidence-based smoking cessation assistance. However, smoking cessation is not routinely provided in general hospital settings (Agrawal and Mangera, 2016), and smoking cessation assistance has been reported as inconsistent, delayed and inadequately delivered in psychiatry inpatient units (Bailey et al, 2019; Kagabo et al, 2020; Metse et al, 2018; Wye et al, 2010). Psychiatry services have traditionally had a permissive approach to smoking (Lawn and Campion, 2013; Ratschen et al, 2018; Sharma et al, 2018; Sheals et al, 2016), with many mental health clinicians reluctant to treat smoking or acknowledge the importance of addressing smoking for people with SMI (Sharma et al, 2018; Sheals et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is unfortunate, as there are a number of treatment options which have been found to be effective for patients in mental health facilities. For example, Metse et al (2018) reported that nicotine replacement therapy was effective according to most psychiatric patients who received it [ 52 ]. According to Keizer et al (2019), motivational enhancement interventions were successful in reducing patients’ tobacco withdrawal symptoms [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…While this is an improvement on other reported rates closer to 50% (Slattery et al, 2016;Wye et al, 2017), it still leaves an unacceptable number of smokers not being treated. Lack of systematic application, challenges in administrative burden and ongoing staff resistance to providing smoking care have been implicated in patients not receiving smoking care (Huddlestone et al, 2018;Koplan et al, 2008;Metse et al, 2018;Wye et al, 2017). The current initiative used an existing hospital clinical pathway to minimise additional administrative effort but also support staff with varying capability levels.…”
Section: Discussionmentioning
confidence: 99%